2017
DOI: 10.1063/1.4997366
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of magnetically dead layers in ferromagnetic thin-films

Abstract: Polarized neutron reflectometry has been used to study interface magnetism and magnetic dead layers in model amorphous CoFeB:Ta alloy thin-film multilayers with Curie temperatures tuned to be below room-temperature. This allows temperature dependent variations in the effective magnetic thickness of the film to be determined at temperatures that are a significant fraction of the Curie temperature, which cannot be achieved in the material systems used for spintronic devices. In addition to variation in the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Experimental details can be found in the supplementary material 32 . We have found that Ta can diffuse vertically within this amorphous alloy during film deposition, and that subtle vertical diffusion of Ta within CFTB causes variation in the local M and T C 33 . This is similar to Fe (100−x) Ta x amorphous alloys, where T C can be tuned from ∼ 200 K to below 100 K by increasing x from ∼ 15 % to ∼ 30 % 34 .…”
Section: Experimental Approachmentioning
confidence: 83%
“…Experimental details can be found in the supplementary material 32 . We have found that Ta can diffuse vertically within this amorphous alloy during film deposition, and that subtle vertical diffusion of Ta within CFTB causes variation in the local M and T C 33 . This is similar to Fe (100−x) Ta x amorphous alloys, where T C can be tuned from ∼ 200 K to below 100 K by increasing x from ∼ 15 % to ∼ 30 % 34 .…”
Section: Experimental Approachmentioning
confidence: 83%
“…Previously, Ta diffusion within the CoFeTaB layer has been observed during the thin-film deposition, which causes variation of magnetization and TC through the thin-film [14]. As many spintronic devices work at elevated temperatures, understanding the Ta diffusion on the magnetic properties of CoFeTaB thin-film is important for the development of spintronic applications.…”
Section: Introductionmentioning
confidence: 99%